2017
DOI: 10.21548/5-1-2363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Yeast Strain, Grape Solids, Nitrogen and Temperature on Fermentation Rate and Wine Quality

Abstract: The effect of four yeast strains, two levels of grape solids, two nitrogen levels and three fermentation temperatures viz. 10°, 13° and 15° C on total fermentation time (TFT) and wine quality was studied in a factorial experiment by employing a nitrogen deficient Chenin blanc must. It was found that the presence of solids, addition of nitrogen and fermenting at 15° C decreased TFT dramatically. Nitrogen was the only factor which also increased wine quality, the other two having a detrimental effect. At optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…The interaction effect of yeast strain and S 0 was significant with regards to fermentation duration ( P = 0.0002, data not shown). Fermentation duration is known to differ among yeast strains and the results of the present study show that effect of S 0 on fermentation rate also differs across yeast strains. The significance of this interaction effect supports the need to employ at least two yeast strains in studies investigating the impact of juice chemistry on fermentation performance.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction effect of yeast strain and S 0 was significant with regards to fermentation duration ( P = 0.0002, data not shown). Fermentation duration is known to differ among yeast strains and the results of the present study show that effect of S 0 on fermentation rate also differs across yeast strains. The significance of this interaction effect supports the need to employ at least two yeast strains in studies investigating the impact of juice chemistry on fermentation performance.…”
Section: Resultsmentioning
confidence: 99%
“…Marly-Brugerolle & Sane, 1978;Ribereau-Gayon, Sudraud & Lafon-Lafourcade 1978;Wenzel & Dittrich, 1978;Williams, Ough & Berg, 1978;Buteau, Duitschaever & Ashton, 1979;Castino, Ubigli & Di Stefano, 1980;Houtman, Marais & Du Plessis, 1980a;Bertrand & Miele. 1984;Tromp. 1984).…”
unclassified
“…However, if these fermentation conditions are too stringently applied, especially with regard to juice clarification, fermentation will be retarded or may even lag (Wucherpfennig & Bretthauer, 1970;Ribereau-Gayon, Lafon-Lafourcade & Bertrand, 1975;Haubs, 1976;Groat & Ough, 1978;Lafon-Lafourcade & Ribereau-Gayon. 1979 -Gayon, 1984;Tromp, 1984). In this respect Houtman & Du Plessis (1986) found that fermentations of juice filtrates of the grape cultivars Colombar, Chenin blanc, Semillon, Cape Riesling and Muscat d'Alexandrie under strictly anaerobic conditions at l5°C required an average of 60 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the latter fermentation and even that of the control treatment experienced lagging and after 80 days residual sugar was in fact still found in the wines. This can probably be attributed to the musts being very clear and virtually devoid of solids (Tromp, 1984;Houtman & Du Plessis, 1986). The 14 + 7 + 3 treatment nevertheless caused an additional lagging of fermentation while the fermentation curves of the musts of the other treatments (not shown) were identical to that of the control.…”
Section: Colombar Field Trialmentioning
confidence: 89%